Finance and Development, March 1981. (Finance and Development; Finance and Development, 1981)
This paper reviews the 'significant impact' of World Bank lending for the rural poor. The paper highlights that a review of 130 World Bank lending operations has found that 94 percent of the total investments completed between 1976 and 1979 have appeared to achieve their major objectives or are well on their way to doing so. And the World Bank's first projects for helping large numbers of poor small farmers have significantly improved farmers' productivity and incomes. Most of the projects were launched in the 1970s.